Evolution of the UV LF from z~15 to z~8 Using New JWST NIRCam Medium-Band Observations over the HUDF/XDF - Bouwens, Rychard J; Stefanon, Mauro; Brammer, Gabriel; Oesch, Pascal A; Thomas Herard-Demanche; Illingworth, Garth D; Matthee, Jorryt; Naidu, Rohan P; van Dokkum, Pieter G; van Leeuwen, Ivana F (arXiv.org, 2023)
We present the first constraints on the prevalence of z>10 galaxies in the Hubble Ultra Deep Field (HUDF) leveraging new NIRCam observations from JEMS (JWST Extragalactic Medium-band Survey). These NIRCam observations probe redward of 1.6\(μ\)m, beyond the wavelength limit of HST, allowing us to search for galaxies to z>10. These observations indicate that the highest redshift candidate identified in the HUDF09 data with HST, UDFj-39546284, has a redshift of z>11.5, as had been suggested in analyses of the HUDF12/XDF data. This has now been confirmed with JWST NIRSpec. This source is thus the most distant galaxy discovered by HST in its >30 years of operation. Additionally, we identify nine other z~8-13 candidate galaxies over the HUDF, two of which are new discoveries that appear to lie at z~11-12. We use these results to characterize the evolution of the UV luminosity function (LF) from z~15 to z~8.7. While our LF results at z~8.7 and z~10.5 are consistent with previous findings over the HUDF, our new LF estimates at z~12.6 are higher than other results in the literature, potentially pointing to a milder evolution in the UV luminosity density from z~12.6. We emphasize that our LF results are uncertain given the small number of z~12.6 sources and limited volume probed. The new NIRCam data also indicate that the faint z~8-13 galaxies in the HUDF/XDF show blue UV-continuum slopes beta~-2.7, high specific star formation rates ~24.5 Gyr**-1, and high EW (~1300A) [OIII]+H\(β\) emission, with two z~8.5 sources showing [OIII]+H\(β\) EWs of ~2300 A.